Influence of Temperature on the Quality of Briquettes in the Giant Miscanthus Densification Process - DEMIANIUK, Leon; DEMIANIUK, Anna Barbara (Engineering Transactions, 2016)
A continuous increase in demand for biomass for energy purposes is the reason why people have begun growing plants known as energy crops, such as common osier, Jerusalem artichoke,giant miscanthus, etc. The power industry most often utilises biomass in the form of pellets and briquettes. One of the basic parameters of the biomass densification process is temperature.This article presents the results of the study about the influence of temperature in the giant miscanthus densification process on the quality of briquettes which are intended for combustion in combined heat and power plants and in stoker furnaces in individual households.